Assessment of Crop Damage By Blackbuck around Blackbuck Conservation Centre, Palasallu, Aligarh, U.P., India - Iqbal, Shahzada; Ilyas, Orus (Indian Forester, 2021)
A need for living provoked conflict between humans and blackbuck (Antilope cervicapra), in and around Blackbuck conservation centre, Palasallu, Gabhana, Aligarh district which arises due to human encroachment of grassland area for agriculture land. Anthropogenic pressure and change in the land use pattern has restricted the habitat of blackbuck into the small Prosopis juliflora, and Prosopis cineraria, in and around (Antilope cervicapra) Blackbuck conservation centre, Palasallu, Gabhana, Aligarh district UP forest, with not much food within but treat of crops all around, thus being the cause of heavy damage to the crops. Examining patterns of conflict and associated tolerance is important to devise policies to reduce conflict impacts on people and wildlife. The survey was done from 120 households from 13 villages within 3 km of Blackbuck conservation Centre which was divided into conflict (8 villages) and non-conflict zone (5 villages). The damage decreased with an increase in distance from the Conservation centre. Blackbuck raided the seedling stage of Wheat (Triticum aestivum), Arhar (Cajanus cajan), and Mustard (Brassica nigra), the most. Guarding was the most effective way for them almost adopted by 34.8% of farmers in the conflict zone. Due to conflict people in the conflict zone are less into farming (32.3%) now, even though 90% of the people are in favour of Blackbuck conservation centre and are proud of it and only ask for better management and policies from the government to mitigate the conflict.